Impact of human activities on green turtle populations in a protected area at Mayotte Island - Goepfert, Melissa (2014)
Marine protected areas are efficient tool for green turtles (Chelonia mydas) conservation. Development of ecotourism in these areas, a form of tourism that is usuallywildlife based and careful of the environment, can contribute to conservation but may alsoresults in disturbances of turtles and habitat degradation. N’Gouja bay (Mayotte Island),protected since 2001, host both nesting and feeding green turtles populations. This area is alsoan attractive site for tourists and residents. A hotel, located behind the beach and wellinvolved in the conservation of marine turtles, offer activities on turtles to its guests, such asobservation of nesting turtles. From 2003 to 2014, N’Gouja beach was monitored for nestingactivity. The frequentation level of the beach by the turtles followed the same pattern that theone observed in other major nesting beaches of the island and stayed constant over the 12years study period. Nesting activities occurs all the year with a peak from April to July.Nesting success was estimated at 42.72 ± SD 4.41 %. However we recorded a heterogeneousnests distribution due to the light pollution emitted by the hotel on the 2008-2014 period. Thefrequentation of the seagrass meadow by green turtles was assess in 2014 and seems notdecrease according to the number of snorkelers. Our results show that human activities andconservation are compatible on condition to establish rules and control human affluence.However, there still is a lack of data available in the literature to assess the impact ofunderwater turtle observation on their behavior and physiology.